Sky songs : meditations on loving a broken world - Sinor, Jennifer, 1969- (American lives., 2020)
Sky Songs is a collection of essays that takes inspiration from the ancient seabed in which Jennifer Sinor lives, an elemental landscape that reminds her that our lives are shaped by all that has passed through.